Global lncRNA expression signature in pre-metastatic lung and their regulatory effects in pulmonary metastasis - Shi, Huifang; Wang, Peng; Wang, Jiaan; Chen, Lei; Qin, Yan; Lv, Jie (Frontiers in Immunology, 2024)
BackgroundLung metastasis has garnered significant attention due to its prevalent occurrence. Pre-metastatic niche (PMN) establishment is a critical prerequisite for the onset of lung metastasis. Emerging evidence indicates that long noncoding RNAs (lncRNAs) play pivotal roles in the metastatic cascade to the lungs. However, the relationship between lncRNA expression profiles and the formation of PMN remains uncharacterized. This study aims to explore the expression profiles and potential roles of lncRNAs in the context of pre-metastatic lung microenvironment.MethodsRNA sequencing was utilized to elucidate the lncRNA landscape in pre-metastatic lung of murine models. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to infer the prospective functions of the differentially expressed lncRNAs. Among these, lncRNA Gm5144-202 in alveolar macrophages (AMs) was further scrutinized for its role in driving M2 macrophage polarization, facilitating the formation of PMN, and orchestrating the apoptosis, proliferation, and migration of tumor cells in vitro.ResultsA total of 232 lncRNAs exhibited differential expression in pre-metastatic murine lungs compared to normal controls, predominantly enriching pathways such as PI3K-Akt signaling, calcium signaling, neuroactive ligand-receptor interaction, and NF-κB signaling. Notably, lncRNA Gm5144-202 exhibited the most pronounced difference, with elevated level in alveolar macrophages (AMs) during the pre-metastatic phase. Silencing of lncRNA Gm5144-202 impeded the polarization of M2-like macrophages, suppressed the expression of factors critical for the formation of the PMN, and inhibited tumor cell invasion.ConclusionsOur research delineated the lncRNA expression profiles in pre-metastatic pulmonary tissues and identified, for the first time, the pivotal role of lncRNA Gm5144-202 in modulating M2 macrophage polarization and tumor cell invasiveness. Consequently, targeting lncRNA Gm5144-202 holds substantial promise for translational applications aimed at mitigating pulmonary metastasis.